2021
DOI: 10.1021/acs.inorgchem.1c01105
|View full text |Cite
|
Sign up to set email alerts
|

Retention of a Four-Fold Interpenetrating Cadmium–Organic Framework through a Three-Step Single Crystal Transformation

Abstract: Controlled hydration leads to four derivatives of a metal–organic framework consisting of cadmium ions, N 1,N 1,N 4,N 4-tetrakis­(4-(pyridin-4-yl)­phenyl)­benzene-1,4-diamine, and coordinated and free nitrates. The balance of water coordination and the multitude of bonding of the weakly coordinated nitrate lead to a progressive change in the coordination number of the Cd2+ ions from eight to seven to six without great perturbation to the 4-fold interpenetration three-dimensional framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…37 The strategy of direct integration of the TPPB ligand with Zn 2+ metal ions afforded a two-dimensional network. To date, several coordination polymers have been reported using the same organic core as the linker; 34,38 however, charge transport behavior in the 2D coordination polymer has remained unexplored.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…37 The strategy of direct integration of the TPPB ligand with Zn 2+ metal ions afforded a two-dimensional network. To date, several coordination polymers have been reported using the same organic core as the linker; 34,38 however, charge transport behavior in the 2D coordination polymer has remained unexplored.…”
Section: Resultsmentioning
confidence: 99%
“…The current application of the TPPB ligand in the coordination framework mainly describes the variation of the crystal structure. 34 By incorporating a redox-active TPPB linker with conjugated organic moieties into the network, we envisage that electron transfer and transport dominate the assembled network. This further urges us to investigate the photocurrent properties of a coordination polymer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 More specifically, the solvent molecules can sometimes act as weakly coordinated ligands to affect the metal coordination sphere, the conformation of organic linkers, and the final network. 8 In other words, organic linkers with conformational flexibility can adopt different configurations during crystallization, which can be seen as solvent-responsive behavior, and can further determine the structural isomerization of CPs. Zhou and Farha et al have recently demonstrated the realization of structurally different Zr-based CPs under different solvent systems with linkers featuring flexible conformations.…”
Section: Introductionmentioning
confidence: 99%
“…23 By introducing a redox-active linker consisting of bis(triarylamine) with a terphenyl unit -N 4 ,N 4 ,N 400 ,N 400 -tetrakis(4-(pyridin-4-yl) phenyl)-[1,1 0 :4 0 ,1 00 -terphenyl]-4,4 00 -diamine (TPPT) into the framework, we sought to investigate the electroactivities of the 3D network. Several frameworks consisting of bis(triarylamine) with single 24 and dual phenyl [25][26][27][28] units as organic ligands have been reported; the predominant role is to employ the core as structure variation. However, the electroactivities of the frameworks have not been explored.…”
mentioning
confidence: 99%